2021
DOI: 10.1007/s40843-021-1773-8
|View full text |Cite
|
Sign up to set email alerts
|

Artificial cathode solid electrolyte interphase to endow highly stable lithium storage of FeF2 nanocrystals

Abstract: Iron difluoride (FeF 2 ) is considered a highcapacity cathode material for lithium-ion batteries. However, its specific capacity and stability are limited by the poor electrochemical kinetics of conversion reactions. Herein, the conversion reaction is confined in a localized nanosized space by encapsulating FeF 2 nanoparticles in polymer gelatin. The FeF 2 nanocrystal-coated polyvinylidene fluoride-based layer (defined as FeF 2 @100%G-40%P) was synthesized by glucoseassisted in-situ gelatinization to construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…It is revealed that Fe/Fe 3 C–Si@CNFs and Si@CNFs have organic fluorine from Li x PO y F z and Li x PF y and metal fluorine from Li–F and Fe–F, indicating that a dense inorganic component of the SEI film contains metal fluorine. 32,54,55 Interestingly, it has been reported that metal fluorine can not only effectively prevent electron tunneling and accelerate the diffusion of Li + in the SEI film but can also prevent the electrode from collapsing during volume expansion/contraction. However, organic fluorine is more likely to produce HF, which can corrode silicon–carbon, affecting the stable long cycling of the LIBs.…”
Section: Resultsmentioning
confidence: 99%
“…It is revealed that Fe/Fe 3 C–Si@CNFs and Si@CNFs have organic fluorine from Li x PO y F z and Li x PF y and metal fluorine from Li–F and Fe–F, indicating that a dense inorganic component of the SEI film contains metal fluorine. 32,54,55 Interestingly, it has been reported that metal fluorine can not only effectively prevent electron tunneling and accelerate the diffusion of Li + in the SEI film but can also prevent the electrode from collapsing during volume expansion/contraction. However, organic fluorine is more likely to produce HF, which can corrode silicon–carbon, affecting the stable long cycling of the LIBs.…”
Section: Resultsmentioning
confidence: 99%
“…Various novel methods have been attempted to stabilize the electrode‐electrolyte interface, such as adding functional additives to the electrolyte or special surface treatments of the electrode. For example, a PVDF‐based artificial CEI layer coated on FeF 2 nanocrystals (FeF 2 @G‐P) was prepared by a one‐step solvent‐thermal method [109] . Owing to the thermal stability and sufficient strength of PVDF, the FeF 2 @G‐P electrode effectively prevents the Fe dissolution and cracking of FeF 2 particles (Figure 7a).…”
Section: Strategies Of Improved Fefx Performancementioning
confidence: 99%
“…For example, a PVDF-based artificial CEI layer coated on FeF 2 nanocrystals (FeF 2 @G-P) was prepared by a one-step solvent-thermal method. [109] Owing to the thermal stability and sufficient strength of PVDF, the FeF 2 @G-P electrode effectively prevents the Fe dissolution and cracking of FeF 2 particles (Figure 7a). As a result, the FeF 2 @G-P composite displayed a discharge capacity of 313 mAh g À 1 at 0.1 A g À 1 over 150 cycles.…”
Section: Surface Modificationmentioning
confidence: 99%
“…The effects of different electrolyte components (salts, solvents, and additives) on the performance of MF-based LIBs/LMBs have been analyzed by resear chers. [85,[203][204][205][206] The CEI film formation due to the decomposition of electrolytes at the cathode is universal and can aid in Small Methods 2023, 7, 2201152 Figure 8. a) Schematic illustration and the cycling ability of LiF/Fe/Cu nanocrystals produced using PLD.…”
Section: Electrolyte and Additivementioning
confidence: 99%
“…The effects of different electrolyte components (salts, solvents, and additives) on the performance of MF‐based LIBs/LMBs have been analyzed by researchers. [ 85,203–206 ] The CEI film formation due to the decomposition of electrolytes at the cathode is universal and can aid in stabilizing the electrode/electrolyte interfaces and preventing further reduction/oxidation of the electrolyte solvent. Hence, the selection and further development of appropriate lithium salts and organic solvents for improving performance are versatile strategies to stabilize CEI films.…”
Section: Improvement Strategiesmentioning
confidence: 99%